A novel lightweight periclase-composite (Mg8-xFex+yAl16-yO32) spinel refractory material for cement rotary kilns. Issue 1 (1st January 2022) - Wu, Han; Chen, Zhe; Yan, Wen; Schafföner, Stefan; Wu, Guiyuan; Dai, Yajie; Li, Yawei
Abstract: This study presents novel lightweight periclase-composite (Mg8-x Fex + y Al16-y O32 ) spinel refractories (LPSR) for the high temperature zone of cement rotary kilns. The LPSR was prepared by using microporous magnesia aggregates instead of sintered magnesia aggregates in traditional periclase-composite spinel refractories (TPSR). Hercynite-corundum composite aggregates, as well as microporous magnesia aggregates with a median pore size of 3.50 μm and a 20.1% lower bulk density than those of the sintered magnesia aggregates were used as raw materials. The microstructures, fracture behavior and strength of the LPSR in contrast with those of the TPSR were determined by SEM and three-point bending tests. After substituting the microporous magnesia aggregates for the sintered magnesia aggregates, a rougher surface of the microporous aggregates and wider transition-layer containing a solid solution spinel phase at the microporous magnesia aggregate/composite spinel aggregate interfaces were observed. Thus, a better bonding at the microporous magnesia aggregate/matrix interfaces as well as of the microporous magnesia aggregate/composite spinel aggregate interfaces was achieved. The wider transition-layer and better interfaces impeded crack propagation along the aggregate/matrix interface and increased the percentage of crack propagation within the aggregates. Thus, the mechanical strength of the LPSR was significantly enhanced. Compared with the TPSR, the LPSR had a lower bulk density of 2.56 g/cm 3, but also a higher apparent porosity of 27.8% and a higher compressive strength of 46.4 MPa.